1994
DOI: 10.1111/j.1476-5381.1994.tb14856.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol and other aliphatic alcohols on NO‐mediated relaxations in rat anococcygeus muscles and gastric fundus strips

Abstract: 1 In anococcygeus muscles, ethanol (20-500 mM) slightly increased the tone and inhibited relaxations elicited by nitrergic nerve stimulation (0.5-5 Hz) in a concentration-dependent manner. 2 Other aliphatic alcohols decreased the tone but had inhibitory effects similar to ethanol on stimulation-induced relaxations, the EC% (mM) values being: methanol 280, ethanol 80, propan-1-ol 20, propan-2-ol 55, propan 1,2-diol 135, butan-l-ol 120, butan-2-ol 15 and pentan-1-ol 3. 3 Relaxations induced by sodium nitroprussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It has been suggested that ethanol and other aliphatic alcohols might interact chemically with nitric oxide to form nitrosylated compounds such as ethyl nitrite, thus sequestering the nitric oxide and explaining their ability to inhibit nitric oxide‐mediated relaxation of rat anococcygeus muscle and gastric fundus ( Rand & Li, 1994 ). The possible nitrosylation of alkanols by nitric oxide seems to be of little significance for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ethanol and other aliphatic alcohols might interact chemically with nitric oxide to form nitrosylated compounds such as ethyl nitrite, thus sequestering the nitric oxide and explaining their ability to inhibit nitric oxide‐mediated relaxation of rat anococcygeus muscle and gastric fundus ( Rand & Li, 1994 ). The possible nitrosylation of alkanols by nitric oxide seems to be of little significance for two reasons.…”
Section: Discussionmentioning
confidence: 99%